Kognisi Taksonomi Bloom, Kurikulum 2013 dan Penerapannya dalam Pembelajaran Agama Islam di Indonesia - Ismail Muhammad; Safrina Ariani (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The use of Bloom Cognitive Taxonomy started since the launching of the book: The Taxonomy of Education Objectives, The Clasification of Educational Goals, Handbook I: Cognitive Domain, published by Longman in the year 1956. The Taxonomy then has been developed by Peter W. Airasian and his friends in their book: A Taxonomi for Learning, Teaching, and Assesing: A Revision of Bloom’s Taxonomy of Educational Objectivesm, A Bridget Edition, edited by W. Anderson and David R. Krathwohl, and published by Addison Wesley Longman, Inc, in 2001. The substantial change of development between the two books is: a) the development of main words from its verb source, b). Bloom separate between the ability of ‘to analyze’ and ‘to synthesize’, while Airasian et.al unites them and put as the 5th cognitive ability, then they propose the ability ‘to create’ as the 6th cognitive ability. The applicative usage of Bloom Cognitive Taxonomy and its revision can be applied fully in the teaching Islamic material, nevertheless, it requires teachers the ability to understand the taxonomy concepts comprehensively and the curriculum applied and the ability to develop and expand main objectives to indicators of instructional activities.